THE ROLE OF GAS ATMOSPHERE FORMING INSIDE HYDRARGYLLITE AND PYRITE GRAINS DURING THE THERMAL DECOMPOSITION OF THE MATERIAL (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
The process of thermal decomposition of hydrargyllite and pyrite has been studied using methods of thermographic and thermogravimetric analyses. It has been approved that the size of grains exerts considerable influence on the whole process of decomposition.
Keywords: thermal decomposition; hydrargyllite; thermographic; thermogravimetric analyses